Traditional Eco-friendly Pest Management Practices in the Dimapur district of Nagaland, India - Nath, Uttam; Puzari, Amrit; Changmai, Shamikhu; Jamir, Temsunungla (Ethnobotany Research and Applications, 2025)
Background: The study was conducted to investigate the phytopesticides used by farmers in the Dimapur district of Nagaland along with their traditional methods of preparation. This study aimed in general to contribute to the modern formulation of plant-based pesticides. Methods: The field survey was conducted in Dimapur district of Nagaland between December 2022 and January 2024. Data was collected through interviews and a semi-structured questionnaire. Results: Thirty-five locally grown phytopesticidal species belonging to 31 genera and 21 families were recorded. Asteraceae and Zingiberaceae possessed the highest number of species, with 4 each followed by Solanaceae and Lamiaceae (3 species each). Twenty types of insect pests were reported. Eight different parts of the plant were used as phytopesticides. The plant part that was used the most was the leaf with 80% of the reports of use. Quantitative indices such as the use value (UV), the family use value (FUV), and the informants consensus factor (ICF) of the phytopesticides were calculated. Azadirachta indica A. Juss has shown the highest use value (0.56). Similarly, Caricaceae showed the highest FUV of 0.52, and Cucurbitaceae and Fabaceae showed the lowest FUV of 0.06 each. The highest ICF value was recorded for gundhi bug (0.98) whereas the lowest ICF was recorded for armyworms (0.94). Conclusions: Five different phytopesticide preparation methods were recorded. Farmers found these formulations to be very effective against insect pests. In the near future, such plants will contribute to the formulation of modern plant-based pesticides with better results. Keywords: Ethnobotany, formulation, insect pests, plant-based pesticides, use value.